Degradation of the pharmaceuticals lamivudine and zidovudine using advanced oxidation processes - Lucena, Alex Leandro Andrade de; Napoleão, Daniella Carla; Silva, Hélder Vinícius Carneiro da; Santana, Rayany Magali da Rocha; Ribeiro, Beatriz Galdino; Duarte, Marta Maria Menezes Bezerra (Ciência e Natura, 2020)
The existence of pharmaceuticals in nature is a growing environmental problem, turning necessary the use of efficient treatments for the degradation of these substances, as the advanced oxidation processes (AOPs). In this work the AOPs UV/H2O2 and photo-Fenton were applied to degrade the pharmaceuticals lamivudine and zidovudine in an aqueous solution using a bench reactor, composed of three UV-C lamps. It was verified that the UV/H2O2 process presented a degradation of 97.33 ± 0.14% for lamivudine and 93.90 ± 0.33% for zidovudine, after 180 min of treatment and for an initial concentratin of each pharmaceutical of 5 mg.L-1 and [H2O2] of 600 mg.L-1. A methodology by artificial neural networks (ANNs) was used to model the photocatalytic process, with the MLP 7-23-2 ANN representing it well, and determining the relative importance (%) of each of the input variables for the pharmaceutical’s degradation process. Kinetic studies for the pharmaceutical degradation and the conversion of organic matter showed good adjustments to the pseudo first-order models with R2 raging from 0.9705 to 0.9980. Toxicity assays for the before treatment solution indicated that the seeds Lactuca sativa and Portulaca grandiflora showed growth inhibition whereas the post-treatment solution inhibited only the growth of Lactuca sativa.